Tingkat Kemampuan Netting dan Backhand pada Atlet Usia 9-14 Tahun di PB TalentaKabupaten Kebumen - AZIS SAPUTRA, YUZA FATHUDIN; Raharjo, Agus (Universitas Negeri Semarang, 2023)
This study aims to determine the ability level of netting and backhand strokes in Pb athletes aged 9-14 years. Talents. This study uses a quantitative approach with descriptive results. Using a survey method with data collection techniques using tests and measurements. The instrument is a test of the ability to hit the netting and backhand. Then the analysis is poured in the form of a percentage. The results show that in the